(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: The aim of the study is to present the results of the research conducted in order to develop a rating system for private security companies operating in Hungary and to provide an insight into the rating systems used in international practice. Methodology: In order to understand the domestic positioning of private security and the international rating systems of private security companies, the author conducted a secondary research and analysis of relevant domestic and international literature, standards and legislation. Findings: Evaluating the experiences of qualification systems introduced in five countries in the field of private security, it can be concluded that certification of private security companies works in practice in the examined states, and databases of qualified companies are available. In general, obtaining a qualification presents a challenge for companies, and possessing it provides them with market advantages. The development and introduction of a certification system is necessary in Hungary as well. Value: Certification of private security companies in Hungary is not yet resolved. The development and introduction of a certification system can give a new impetus to the development of the profession, promote the "whitening" of the sector, the development of companies, and the elevation of the profession’s prestige. The final result will be an increase in the value of services provided by the sector.